(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
Western European public policy includes end-of-life situations. Ergo, an in-depth investigation here analyzes the Albanian legislature relating to end-of-life decisions by concentrating on the role of legal proxy in end-of-life decisions. This paper explores the Albanian legal system, national medical jurisprudence, with special attention paid to the Code of Medical Ethics. Also included are publications written by the two main advisory public bodies on health issues: the National Ethics Committee and the National Committee of Health. Following a discussion of the fundamental role of a legal proxy in end-of-life decisions, and taking into account the experience of some Western European countries, some policy suggestions become clear. In the conclusion, this paper emphasizes the need for ad hoc legislature to establish the role of legal proxy in end-of-life decisions as well as the utilization of the international framework as a source of guidance to address the shortcomings in the national system in the interim.